Clinical Characteristics, Virulence Profile, and Molecular Epidemiology of Klebsiella pneumoniae Infections in Kidney Transplant Recipients - Fan R; Zuo Y; Wang B; Shi D; Wang X; Wang Z; Huang Y (Infection and Drug Resistance)
Ruiling Fan,1 Yan Zuo,1 Bowei Wang,2 Debao Shi,1 Xuanxuan Wang,1 Zhongxin Wang,1 Ying Huang1 1Department of Clinical Laboratory, The First Affiliated Hospital of Anhui Medical University, Hefei, Anhui, 230022, People’s Republic of China; 2Department of Clinical Laboratory, The Third Affiliated Hospital of Anhui Medical University, The First People’s Hospital of Hefei, Hefei, Anhui, 230061, People’s Republic of ChinaCorrespondence: Ying Huang; Zhongxin Wang, Department of Clinical Laboratory, The First Affiliated Hospital of Anhui Medical University, No. 218 Jixi Road, Hefei, Anhui, 230032, People’s Republic of China, Tel +8613855102425 ; +8613866709500, Email huangying_ah2007@sina.com; aywzhx87@163.comBackground: Carbapenem-resistant Klebsiella pneumoniae (CRKP) infections may increase the potential for mortality in kidney transplant (KT) recipients. This study aimed to investigate the clinical features, molecular epidemiology, virulence, and antimicrobial resistance of KP strains from KT patients.Methods: Strains isolated from KT patients were collected, and antimicrobial susceptibility analysis was verified via the Vitek2 compact instrument and the disc diffusion method. In gene expression analysis, carbapenemase genes (KPC-2, OXA-48, IMP, VIM, NDM), capsular genes (K1, K2, K5, K20, K54, K57), and virulence genes (rmpA, rmpA2, aerobactin, peg344) were identified via polymerase chain reaction (PCR). Molecular epidemiology was analyzed using multilocus sequence typing (MLST) and minimal spanning trees (MST).Results: A total of 43 KP isolates were collected from KT patients in this study, and 24 of them were identified as CRKP (55.81%). KPC-2 genes were detected in all of the CRKP strains (100%), and other carbapenemase genes were not detected. Twenty-two strains (91.67%) of CRKP strains were identified as ST11, while 2 (8.33%) were ST15-typing. Finally, two highly virulent K. pneumoniae strains (both K20-ST268 type) were identified. In addition, the group of CRKP showed a higher deceased kidney donor ratio (p = 0.011), a higher proportion of post-transplant transfers to the ICU (p = 0.037), a higher proportion of late-onset infections (3 months post-transplantation acceptance) (p = 0.007), and high positive rates for the virulence gene rmpA2 (p = 0.01) when comparing the group of carbapenem-sensitive KP.Conclusion: The resistance rate to carbapenem of KP from KT patients exceeded the regional average with predominant ST typing of ST11. Clinical data were analyzed to derive some high-risk factors for CRKP infection. Therefore, we recommend early prophylactic isolation of transplant patients with high-risk factors for CRKP infection to improve the quality of nosocomial control.Keywords: kidney transplant, Klebsiella pneumoniae, virulence gene, multilocus sequence typing